Minimally Invasive Management of Diverticular Disease - Madiedo, Andrea; Hall, Jason (Clinics in Colon and Rectal Surgery, 2021)
Traditionally, management of complicated diverticular disease has involved open damage control operations with large definitive resections and colostomies. Studies are now showing that in a subset of patients who would typically have undergone an open Hartmann's procedure for Hinchey III/IV diverticulitis, a laparoscopic approach is equally safe, and has better outcomes. Similar patients may be good candidates for primary anastomosis to avoid the morbidity and subsequent reversal of a colostomy.While most operations for diverticulitis across the country are still performed open, there has been an incremental shift in practice toward minimally invasive approaches in the elective setting. The most recent data from large trials, most notably the SIGMA trial, found laparoscopic sigmoid colectomy is associated with fewer short-term and long-term complications, decreased pain, improvement in length of stay, and maintains better cost-effectiveness than open resections. Some studies even demonstrate that robotic sigmoid resections can maintain a similar if not more reduction in morbidity as the laparoscopic approach while still remaining cost-effective.Intraoperative approaches also factor into improving outcomes. One of the most feared complications in colorectal surgery is anastomotic leak, and many studies have sought to find ways to minimize this risk. Factors to consider to minimize incidence of leak are the creation of tension-free anastomoses, amount of contamination, adequacy of blood supply, and a patient's use of steroids. Techniques supported by data that decrease anastomotic leaks include preoperative oral antibiotic and mechanical bowel prep, intraoperative splenic flexure mobilization, low-tie ligation of the inferior mesenteric artery, and use of indocyanine green immunofluorescence to assess perfusion.In summary, the management of benign diverticular disease is shifting from open, morbid operations for a very common disease to a minimally invasive approach. In this article, we review those approaches shown to have better outcomes, greater patient satisfaction, and fewer complications.
Keywords: complicated diverticulitis; minimally invasive sigmoidectomy; laparoscopic sigmoidectomy; robotic sigmoidectomy; inferior mesenteric artery (IMA) ligation; splenic flexure mobilization; ICG immunofluorescence